President Obama’s Approach to Democracy Promotion in the MENA Region - BIOUD, Hadjer; HAMADOUCHE, Fatima (Journal of Human Sciences, 2025)
This article examines former U.S. President Barack Obama’s approach to promoting democracy in the Middle East and North Africa (MENA) region amid critiques and strategic shifts. It highlights his initial "Three Ds" strategy, standing for diplomacy, development, and defense, which excluded democracy as a direct focus, marking a departure from his predecessor’s Freedom Agenda. Central to this shift was President Obama’s 2009 Cairo speech, proposing a "New Beginning" with Muslim-majority nations and adopting softer rhetoric on democracy. However, the Arab uprisings challenged this strategy, leading to nuanced responses across Tunisia, Egypt, Libya, Syria, Bahrain, and Yemen. The article also explores the post-Arab Spring period, where declining democracy funding raised questions about the administration’s priorities and commitment to democratic ideals in the region.